Nutritional cardiomyopathy in a young camel (c. dromedarius) - Özgür Özdemir; Mustafa Kemal Çiftçi; Fatih Hatipoğlu; Mustafa Ortatatlı; Orhan Yavuz; Özgür Kanat (Eurasian Journal of Veterinary Sciences)
In this report, macroscopical and microscopical findings of nutritional cardiomyopathy were firstly described in a 1.5 month old female calf-camel in Turkey. At the necropsy of the young camel, which was found as dead in Konya Karatay Municipality Zoo, pale, whitish colored areas were seen on the epicardium of heart ventricules and interventricular septum. The pale areas were more prominent in the left heart ventricle. Lung was fairly volumed and dark reddish colored, and there was foamy fluid in trachea and bronchi. Mediastinal and bronchial lymph nodes were enlarged, and cut surfaces were dark red colored. Congestion in the liver and enlargement in thyroid glands were also observed. In microscopical examination of the heart muscle, hyaline degeneration, Zenker's necrosis and widespread calcification were determined. In lung, diffuse congestion and edema in alveoli were found. Mild hyperemia in sinusoids of the liver, degeneration and desquamation of lamina epithelialis, neutrophil and eosinophil granulocyte infiltration in lamina propria in small intestine were noticed too. Papillary extensions in epithelium of thyroid follicles due to epithelial hyperplasia were observed. It was concluded from these findings that inadequate nutrition probably caused white muscle disease, resulting in blood circulation disorder in lungs, in the young camel. So, it is advisable to have a vitamin and mineral supplement to animal especially within the enclosed areas like zoos.